Lgr6: From Stemness to Cancer Progression - Cortesi, Emanuela (J Lung Health Dis, 2019)
Lung cancer is the leading cause of cancer-related deaths worldwide with poor prognosis, mainly due to the delay in the diagnosis. Adenocarcinoma, a subtype of non-small cell lung cancer, has the highest incidence and significant recurrence rates. Experimental and clinical researches suggested that the presence of cancer stem cells could support the development, malignization and resistance of lung cancer. Unfortunately, our knowledge in the field is still limited. Here we report our findings regarding a cell population expressing LGR6, an epithelial stem cell marker. Under the pressure of a fine regulated p38α MAPK/mir-17-92 axis, LGR6(+) stem cells produce differentiated bronchioalveolar cells, in the normal lung. LGR6 is enriched in tumour cells during adenocarcinoma progression. Similar to normal stem cells, LGR6(+) cancer cells show self-renewal and differentiation capacities, alongside with a higher oncogenic potential. Our studies suggest a disruption in the p38α MAPK/mir-17-92 network, that enhances Wnt pathway activity, could be responsible for the selection of malignant LGR6(+) tumour cells. These results support the existence of a cell population with stem-like characteristics and strong oncogenic potential. This population could be useful for predictive diagnosis and a novel target for improved and more effective therapies against metastases and recurrences of lung adenocarcinomas.